Culture of Speech – Category of the State - Svitlana Kolomiyets; Alina Kachur (Pedagogical Discourse, 2013)
The culture of speech, its components, their role in communication, causes of doublespeak is considered. The role of the state language in strengthening the unity of the state is determined. The author pecified the priority features of the Ukrainian language in comparison with other languages. Specific examples considered of the regulation of the norms of Ukrainian literary language. It outlined the influence of the media on the formation of a linguistic personality. Unsolved questions about the role of the teacher's speech in the humanitarian development of pupils. The causes of Russification, impoverishment of the Ukrainian language and the methods of protection of his beauty, wealth, nation- and state-formation power of the language are discussed. The ways to overcome the low speech culture are suggested.